The Impact of Education and Training on The Success of Small and Medium-Sized Enterprises - Saah, Paul (Journal of Economics Education and Entrepreneurship, 2022)
Many business management researchers regard the small and medium-sized enterprise sector as the pillar and primary impetus of economic growth, particularly in developing countries. As a result, most governments throughout the world now place a strong emphasis on small business development to spur economic growth. The purpose of this study was to see how education and training affected the success of small businesses. This study uses a qualitative research approach to collect and analyse data. The study’s 20 small business owners and managers in South Africa were selected using a non-probability sampling approach. Data was collected through interviews, and the results were analysed using subject analysis. This study’s findings reveal that a lack of human capital education and training is one of the primary causes of SMEs’ high failure rate, which also explains why these enterprises fail so frequently in most countries. It is evident that small business owners and managers, particularly in most developing nations such as South Africa, should consider spending more on business education and training to gather information that would help them establish unique business strategies.